GENETIC ASPECTS OF MULTIPLE MIELOMA - Yatsenko, L.D. (World of Medicine and Biology, 2016)
Multiple myeloma (MM) is characterized by significant heterogeneity of clinical displays, biological characteristics and effect on treatment. Data, received today, pointed to the hypothesis, that this toxicity is caused by molecular characteristics of the tumor clone. Kariоtype at (MM) is complex of cause, including quantity (amount of chromosomes), and quality (structure of chromosomes) components.